Effect of gully headcut treatment on sediment load and gully expansion in the sub humid Ethiopian Highlands - Zegeye, Assefa D.; Steenhuis, Tammo S.; Mekuria, Wolde; Dagnaw, D.C.; Addisse, M.B.; Tilahun, Seifu A.; Kasse, T.A. (Horizon Research Publishing Co., Ltd., 2017)
The Ethiopian government has been implementing a land restoration program that aimed to restore degraded ecosystems and double agricultural productivity throughout the country since 2010. However, the success of the restoration program has been limited due to the lack of integrating gully erosion control measures. Consequently, many reservoirs in Ethiopia and downstream riparian countries have lost their storage capacity due to sedimentation, and studies demonstrated that gully erosion is one of the degradation hotspots within watersheds and contribute considerable proportion of the total sediment loads from a particular watershed. This study was conducted in one of large gullies in the Debre-Mawi watershed, northwestern Ethiopia to quantify the effect of gully head treatment in reducing the amount of sediment load generated from uplands and from the gully itself. We measured discharge, and sediment load and concentration in 2013 and 2014 at the upstream (inlet) and downstream ends (outlet) of the studied gully. Before the 2014 rainy phase, a gully headcut was stabilized with gabions at the bed and the gully bank was regarded to 45o. The gully head retreated 12 m in 2013 but gully head retreat was stopped following the implementation of the treatment in 2014. The total sediment load and sediment concentration at the outlet was reduced by 42% and 30% respectively, in 2014 (i.e., after treatment) when compared to 2013 (i.e., before treatment). The result of this study support that controlling the upward retreat of gully head is effective in reducing sediment load and concentration as well as upward movement and expansion of gullies. However, maintenance of gully head control measures is the key to sustain the benefits.